A Design Study of a Learning Model for Chinese International Students in Thai Universities - Suacamram, Mayuree; Li , Lin; Luo , Qiuxue; Roung-onnam , Rapassa; Banphato , Pailin (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
This research investigated the learning styles of Chinese international students at Thai universities and designed a corresponding learning model. Employing a mixed-methods approach, quantitative data were collected via questionnaires from 320 students, and qualitative data were gathered through interviews with 12 students. Quantitative data were analyzed using cross-tabulation and chi-square tests; qualitative data were analyzed using content analysis. Results revealed significant differences in the active-reflexive learning styles of male and female students: males exhibited a more active learning style, preferring group work and problem-solving activities, while females demonstrated a more reflexive style, favoring independent problem-solving and analytical thinking. Qualitative findings indicated that these students were highly motivated, patient, analytically inclined, and committed to self-directed learning through practical application and observation. Based on these findings, the proposed learning design guidelines for Chinese international students emphasize student-centered learning, practical application, collaborative activities, critical thinking, and collaborative reflection.